Multi-criteria decision-making model for assessing the sustainability index of wind-turbine support systems: application to a new precast concrete alternative. Issue 2 (17th February 2017) - de la Fuente, Albert; Armengou, Jaume; Pons, Oriol; Aguado, Antonio
Abstract: A multi-criteria decision-making system based on the MIVES method is presented as a model for assessing the global sustainability index scores of existing wind-turbine support systems. This model is specifically designed to discriminate between tower systems in order to minimize the subjectivity of the decision and, thus, facilitate the task of deciding which system is best for a given set of boundary conditions (e.g., height, turbine power, soil conditions) and economic, social and environmental requirements. The model's versatility is proven by assessing the sustainability index of an innovative new precast concrete tower alternative also described in this paper. As a result of this analysis, some points of improvement in the new system have been detected.